2014
DOI: 10.3945/jn.113.189589
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation Benefits Physical Performance in Women of Reproductive Age: A Systematic Review and Meta-Analysis

Abstract: Animal and human observational studies suggest that iron deficiency impairs physical exercise performance, but findings from randomized trials on the effects of iron are equivocal. Iron deficiency and anemia are especially common in women of reproductive age (WRA). Clear evidence of benefit from iron supplementation would inform clinical and public health guidelines. Therefore, we performed a systematic review and meta-analysis to determine the effect of iron supplementation compared with control on exercise p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 49 publications
3
124
1
6
Order By: Relevance
“…The studies with the largest effect sizes had initial values <40 mL/kg/min24 27 28 compared to studies which showed no effect (>45 mL/kg/min), suggesting a greater potential for enhancement, particularly if the iron supplementation was combined with aerobic training. A recent meta-analysis investigating the effects of oral iron supplementation in women of reproductive age also reported significant effects on relative and absolute (increase of 2.35 mL/kg/min; 95% CI 0.82, 3.88 and 0.11 L/min; 95% CI 0.03 to 0.20, respectively) 54. Despite not being specific to iron deficiency or endurance athletes, this does support the suggestion that iron supplementation can enhance aerobic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…The studies with the largest effect sizes had initial values <40 mL/kg/min24 27 28 compared to studies which showed no effect (>45 mL/kg/min), suggesting a greater potential for enhancement, particularly if the iron supplementation was combined with aerobic training. A recent meta-analysis investigating the effects of oral iron supplementation in women of reproductive age also reported significant effects on relative and absolute (increase of 2.35 mL/kg/min; 95% CI 0.82, 3.88 and 0.11 L/min; 95% CI 0.03 to 0.20, respectively) 54. Despite not being specific to iron deficiency or endurance athletes, this does support the suggestion that iron supplementation can enhance aerobic capacity.…”
Section: Discussionmentioning
confidence: 94%
“…However, the studies are small, heterogeneous in design, and not always unbiased. 32 Iron supplementation in very young preschool children living in low-income areas may correct anemia, but a large meta-analysis of randomized trials failed to find evidence of improved cognitive performance or positive effect on growth and development. 33 In endemic malarial areas iron supplementation raises the concern of increasing parasitemia or even clinical malaria.…”
Section: Oral Iron Supplementationmentioning
confidence: 99%
“…Although the aerobic exercise improves the functional parameters of RA, its effects on the path physiology of the disease remain to be elucidated. The exercise, especially the aerobic subgroup, in healthy individuals result in increased total Hb concentration, HCT, and red blood cell (RBC) mass [42]. The aim of the current study is to investigate the effects of moderate aerobic exercise on the Hb, HCT, and RBC mass of women with RA.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian National Physical Activity Guidelines for Adults recommend that for good health, "adults should put together at least 30 min of moderate intensity physical activity on most, preferably all, days." The aerobic exercise has been shown to be associated with increased RBC mass, Hb, and HCT in healthy individuals [42]. During the current study we tried to determine the effects of aerobic exercise on hematologic indices of women with RA.…”
Section: Discussionmentioning
confidence: 99%